Carbon pool in different land use in Germany - Normah Awang Besar @ Raffie; M.S. Idris; CH Tan (Malaysian Agricultural Research and Development Institute (MARDI), 2015)
The impact of land use on carbon pools were investigated in three different land use type (forestland, arable land and grassland) in Katinger Watt area in Northern Germany. The area was once a sea floor (tidal flat) that was dyked in 1973. Relevant condition for carbon turnover in the studied area were similar, thus the different in carbon pools during soil genesis were attributed to different land use systems.